The European Green deal and human security : the case of European Union-African Union relations - Tiftikçi Hermes, Yağmur (My University, 2024)
Bu tez, Avrupa Birliği'nin (AB) küresel iklim politikalarındaki aktörlüğünü, insan güvenliği yaklaşımıyla değerlendirmektedir. Özellikle, mevcut ilişkiler göz önünde bulundurularak Avrupa Yeşil Mutabakatı (AYM)'nın AB-Afrika Birliği ilişkilerini nasıl etkileyebileceğini analiz etmektedir. Analiz için AYM’nin beş farklı ana politika alanı seçilmiştir: sera gazı emisyonlarının azaltılması, enerji dönüşümü, biyoçeşitlilik ve sürdürülebilir tarım, döngüsel ekonomi ve bu planların finansmanı için AB fonları ve yatırımları. Belirtilen politika alanlarının insani güvenlik yaklaşımının prensipleri ile uyumlu olup olmadığı bu tezin ana analiz konusudur. Analizin yapılabilmesi için ilk olarak insani güvenlik kavramının genel tanımları yapılır ve ardından AYM’nin kapsamı ve politikaları ile AB ve Afrika Birliği arasındaki tarihi ve mevcut ilişkiler derinlemesine incelenir. Tezin ana argümanı, AYM'nin AB-Afrika Birliği ilişkilerini nasıl etkileyeceğini analiz ederken insan güvenliği yaklaşımının benimsenmesinin, hem iklim krizinden hem de düşük karbonlu ekonomiye geçişle ilgili adillik sorunlarından kaynaklanan bazı zorlukları anlamak ve çözmek için daha sağlam bir zemin sağlayabileceğidir. Tez ayrıca, Afrika Birliği'ndeki artan insan güvenliğinin, bölgelerin yakınlığı nedeniyle dolaylı olarak AB'deki insan güvenliğine katkıda bulunacağını ileri sürmektedir.

This thesis evaluates the European Union’s (EU) actorness in global climate politics by reviewing the European Green Deal (EGD) with the human security approach. It mainly analyzes how the EGD impacts the EU’s relations with the African Union (AU). It focuses on five different key policy areas under the EGD – reducing greenhouse gas emissions, energy transition, biodiversity and sustainable agriculture, circular economy, and, to finance all of these plans, the EU funds and investments – to analyze whether these policy areas can be explained through the analytical framework of human security. To do so, the thesis provides a detailed definition of human security; scrutinizes the scope and policies of the EGD, and finally analyses the history and current relations of the EU with the AU. The main argument of this thesis is that although the term human security has not been used in the EGD Communication document, the EGD has a human security dimension. Therefore employing a human security approach in the analysis of how the EGD would impact EU-AU relations can provide a better ground to understand and resolve challenges arising from both the climate crisis itself and fairness issues related to the transition to a low-carbon economy both in the EU and the AU. The thesis also claims that the increased human security in the AU would indirectly contribute to human security in the EU due to the proximity of the regions.
Keywords: Afrika Birliği; Avrupa Birliği; Avrupa Yeşil Mutabakatı; Climatic changes; Çevresel yönleri; Environmental aspects; European Union; İklim değişikliği; İnsani Güvenlik Yaklaşımı; Küresel İklim Politikaları Global Climate Politics; The African Union; The European Green Deal; The European Union; The Human Security Approach